Promoção do aleitamento materno pelo enfermeiro atuante na atenção primária à saúde: revisão de escopo - Avelar, Emily Rezende (2023)
Introduction: Exclusive breastfeeding is recommended until six months of age and continued breastfeeding for up to two years or more. In this context, the nurse on the Primary Health Care team plays an important role in health promotion. General objective: to map the evidence available in the literature on strategies used by nurses working in Primary Health Care to promote, prevalence and duration of breastfeeding. Method: scoping review guided by the question: What evidence is available in the literature on strategies used by nurses working in primary health care for the promotion, prevalence and duration of breastfeeding? The research was carried out in national and international databases and gray literature. Results: 1,380 studies were retrieved, of which 486 were excluded due to duplication and 820, after reading the title and abstract, because they did not meet the inclusion criteria. One study was removed because it was not freely available. 73 studies were evaluated in full. Of these, 27 were excluded because they did not meet the inclusion criteria. Two studies were added after reading the references of the included studies, totaling 48 studies in this scoping review. The present work made it possible to outline a scope of publications that addressed the topic, in the period considered, and to fulfill the objectives of analyzing scientific production on strategies for promoting breastfeeding by primary health care nurses. Final considerations: It could be seen that there was a tendency to increase in the number of publications on the subject, scientific production is mostly Brazilian and produced by nurses in public universities, but it is not extensive, directing the need for new research, aiming at publications in high-profile journals for greater visibility in the global scientific community. Carrying out health education actions, through nursing consultations, was the most cited individual strategy. It is added that special attention should be directed to women in the postpartum phase, through guidance on breastfeeding and breastfeeding assessment, in addition to the inclusion of family members, partners and the support network in health education actions. In relation to collective strategies, group health education prevailed, be it groups of pregnant women, nursing mothers and peer support for breastfeeding. Regarding the potential for organizing and planning the nurse's work process, the importance of creating public policies and structured government programs to support breastfeeding was evident, as well as a consistent approach to the topic in professional training, the implementation of ongoing education of the team and management of breastfeeding promotion actions. As weaknesses, the studies pointed out that there is little implementation of actions to promote breastfeeding in PHC, precarious working conditions for nurses and a lack of organization of their work process, a panorama that needs to be modified with the utmost urgency, given the importance of breastfeeding.